Pengembangan Desa Muntigunung sebagai Desa Wisata Baru di Kecamatan Kubu Kabupaten Karangasem - Ariawan, I Wayan Adi Putra; Antara, Made; Arida, I Nyoman Sukma (JURNAL MASTER PARIWISATA, 2021)
Muntigunung Tourism Village is currently designated as a tourist village by the Karangasem Regency Government. The reason of Muntigunung Tourism Village as a new tourism village in Karangasem Regency because Muntigunung Tourism Village has natural beauty that is still natural, a culture that is still traditional and expected to minimize the level of poverty and beggar activities carried out by the Muntigunung Tourism Village community. This research analyzes the development strategy of Muntigunung Tourism Village. The data can be described descriptively qualitatively and analyzed using SWOT analysis techniques. The research of this study indicate that the strategy S-O (strengts-opportunities) that is applied aims to use the power possessed by utilizing the opportunities that exist. The S-T Strategy (Strenghts-Threats) that is applied aims to utilize the strength that is possessed to minimize existing threats. W-O (weakness-opportunities) strategy that aims to minimize weaknesses that are owned by exploiting opportunities. W-T (Weakness-Threats) strategies are implemented to minimize weaknesses to avoid threats. Keywords: SWOT, Development Strategy, Tourism Village